Transformation of tax instruments to stimulate investment processes - E. L. Gulkova; M. V. Karp; M. V. Tipalina (Вестник университета)
The article examines the practice of applying various tax instruments to stimulate largescale investment processes. The purpose of the study is to analyse tax instruments to stimulate these investment processes from the point of view of their impact on the final outcome. The authors decided tasks: to consider the taxes benefits and preferences as tools for stimulating large-scale investment processes; to identify opportunities for creating the most favorable tax climate for these investment projects; to assess the possibility of expanding such a tax administration tool as tax monitoring, subject to the inclusion of organisations implementing large investment projects as taxpayers. The authors’ recommendations and conclusions can be used in the development of conceptual provisions of tax policy both at the regional and state level in the field of tax regulation of investment processes.